MORE PRACTICE WITH THE FORM   $\displaystyle a\cdot\frac{b}{c}$
Simplify: $\displaystyle\,4\cdot\frac{3}{2}$

$\displaystyle 4\cdot\frac{3}{2} = \frac{4}{2}\cdot 3 = 2\cdot 3 = 6$

You should be able to go from the original expression to the final answer without writing anything down.
The solution above shows the thought process.
Always be on the lookout for factors in the denominator that go into factors in the numerator evenly!
Simplify: $\displaystyle \,\frac{-3}{-5}\cdot -10$

$\displaystyle \frac{-3}{-5}\cdot -10 = - \frac{10}{5}\cdot 3 = -2\cdot 3 = -6$

Here, use a two-step process:
Master the ideas from this section
by practicing the exercise at the bottom of this page.

When you're done practicing, move on to:
Renaming Fractional Expressions

Simplify. Do NOT use a calculator!
(an even number, please)